Relationship of Chemistry Teachers’ Knowledge, Skills and Affective on Computer-Assisted Learning - Aliyu, Hassan; Abdullahi, Anas; Abdul Talib, Corrienna; Aliyu, Faruku; Umar Mani, Bilkisu (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The study investigated the relationship of chemistry teachers’ knowledge, skills and affective on computer-assisted learning in Sokoto. A questionnaire was designed and distributed to 81 chemistry teachers in 24 secondary schools in the metropolis. The premises that guide the development of the test items used are strongly based on constructivism theory of learning and related literature. The data obtained from an online survey (Google form) were imported into an excel spreadsheet which was later keyed into SPSS 25 for further analysis. The results indicated that Chemistry teachers of Sokoto are have moderate level of both knowledge, skills and affective of computer-assisted learning. The results reveals that both knowledge, skills and affective serves independent purpose for instruction that utilizes computer-assisted learning. It concluded that the moderate knowledge, skills or affect are not significant for integrating computer-assisted learning in chemistry instruction. Awareness alone cannot guarantee quality integration of instruction in the classroom. Thus, chemistry teachers should seek more professional training on computer-assisted learning through workshop, seminars and conferences.Keywords: knowledge, skills, affective, computer-assisted learni